Diet Quality Index of Infants Aged 6–9 Months of the Baduy Luar Ethnic Group in Lebak Regency, Indonesia - Vidyarini, Andra; Muzakir, Haris (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2023)
The study aim was to determine the quality of food consumption using the Diet Quality Index for Infants aged 6 to 9 months from Baduy Luar Ethnic Group. The study was conducted in 16 hamlets of Kanekes Village and the sample size was 79 infants. The data were consumption data of infants for one week based on Semi Quantitative Food Frequency Questionnaire (SQ-FFQ). Diet quality results are classified into good, fair and poor. Most of the toddlers consumed breast milk and had low intake of protein, vegetables, fruits while their carbohydrate consumption was in accordance with recommendations. This study shows that quality of food consumption is not associated with nutritional problems in infants.